A Broad Range of Dose Optima Achieve High-level, Long-term Gene Expression After Hydrodynamic Delivery of Sleeping Beauty Transposons Using Hyperactive SB100x Transposase - Kelly M Podetz-Pedersen; Erik R Olson; Nikunj V Somia; Stephen J Russell; R Scott McIvor (Elsevier, 2016)
The Sleeping Beauty (SB) transposon system has been shown to enable long-term gene expression by integrating new sequences into host cell chromosomes. We found that the recently reported SB100x hyperactive transposase conferred a surprisingly high level of long-term expression after hydrodynamic delivery of luciferase-encoding reporter transposons in the mouse. We conducted dose-ranging studies to determine the effect of varying the amount of SB100x transposase-encoding plasmid (pCMV-SB100x) at a set dose of luciferase transposon and of varying the amount of transposon-encoding DNA at a set dose of pCMV-SB100x in hydrodynamically injected mice. Animals were immunosuppressed using cyclophosphamide in order to prevent an antiluciferase immune response. At a set dose of transposon DNA (25 µg), we observed a broad range of pCMV-SB100x doses (0.1-2.5 µg) conferring optimal levels of long-term expression (>1011 photons/second/cm2). At a fixed dose of 0.5 μg of pCMV-SB100x, maximal long-term luciferase expression (>1010 photons/second/cm2) was achieved at a transposon dose of 5-125 μg. We also found that in the linear range of transposon doses (100 ng), co-delivering the CMV-SB100x sequence on the same plasmid was less effective in achieving long-term expression than delivery on separate plasmids. These results show marked flexibility in the doses of SB transposon plus pCMV-SB100x that achieve maximal SB-mediated gene transfer efficiency and long-term gene expression after hydrodynamic DNA delivery to mouse liver.